2020
DOI: 10.1007/s12564-020-09636-y
|View full text |Cite
|
Sign up to set email alerts
|

Do the conditions in Chinese secondary school education imply a need for global citizenship education? An exploration of six secondary schools in Jiangsu

Abstract: Global citizenship education (GCE), an educational advocacy for students to attain the competencies of being aware of and actively engaged in defending social justice, equity and sustainable development at both local and global levels, is difficult to achieve in practice. The failure can be attributed to inadequate knowledge of different effects of GCE when it is used to meet specific needs of local schools. Identifying local schools' needs for GCE may help educators put GCE to good use. However, few studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…Together, these initiatives can assist in maintaining support for a more meaningful global citizenship education in the face of the many challenges of the current educational context. Hong (2020) The results showed that most respondents perceived CAS to have had a positive impact, particularly for developing individual skill sets. Respondents agreed that participating in CAS broadens their perspectives, but they reported little change in their behavior or worldview as a result.…”
Section: Citizenship Educationmentioning
confidence: 94%
“…Together, these initiatives can assist in maintaining support for a more meaningful global citizenship education in the face of the many challenges of the current educational context. Hong (2020) The results showed that most respondents perceived CAS to have had a positive impact, particularly for developing individual skill sets. Respondents agreed that participating in CAS broadens their perspectives, but they reported little change in their behavior or worldview as a result.…”
Section: Citizenship Educationmentioning
confidence: 94%
“…Finally, from a pragmatist perspective, which is the third rationale, GCE is often acknowledged via a competency-based framework. Hong ( 2020 ) conducted a situational analysis through a selected case of six secondary schools on the east coast of China and found GCE implemented through competency-based education. However, based on the results of the situational analysis, GCE only offers subtle benefits to competency-based education—unsurprising given that a competency framework lacks the epistemic foundation (Ryen & Jøsok, 2021 ) for guiding teaching.…”
Section: The Likely Role Of Global Citizenship Education In the Curriculummentioning
confidence: 99%
“…However, based on the results of the situational analysis, GCE only offers subtle benefits to competency-based education—unsurprising given that a competency framework lacks the epistemic foundation (Ryen & Jøsok, 2021 ) for guiding teaching. As Table 1 shows, this research case involved students with low socioeconomic status, and the schools prioritized improving academic performance to ensure social mobility (Hong, 2020 ). Asian societies that emphasize Confucianism tend to value meritocracy along with the moral aspect of GCE.…”
Section: The Likely Role Of Global Citizenship Education In the Curriculummentioning
confidence: 99%
See 2 more Smart Citations